Relationship Between Clinical Findings, Quality of Life and Functional Disability Related to Disease Activity in Patients with Ankylosing Spondylitis - Kemal NAS; Remzi ÇEVİK and Mehtap BOZKURT and Ali GÜR and Ayşegül Jale SARAÇ (Archives of Rheumatology, 2011)
Objectives: In this study we evaluated the relationships between clinical findings, quality of life and functional disability related to disease activity in patients with ankylosing spondylitis (AS). Patients and methods: Seventy-three patients diagnosed with AS (62 males, 11 females; mean age 33.3±9.5 years; range 17 to 60 years) who fulfilled the modified New York criteria were included in this study. The mean age for female patients was 29.2±7.3 years and for males 34.0±9.7 years. The demographic data of the patients were recorded. The disease activity was assessed using the Bath ankylosing spondylitis disease activity index (BASDAI). The functional disability was evaluated using the Bath ankylosing spondylitis functional index (BASFI). The clinical status was evaluated with the Bath ankylosing spondylitis metrology index (BASMI) and the quality of life was assessed with the Short Form 36 (SF-36). Results: The patients were divided into two groups: patients having a BASDAI score of less than four (BASDAI <4) with mildly active disease (n=34) and patients having a BASDAI score of four or higher (BASDAI ≥4) with moderate-severe disease activity (n=39). The BASFI and BASMI scores were higher in patients with high disease activity (p<0.05), and a significant correlation was found between the BASDAI total score and the BASFI and BASMI scores (p<0.05). Patients with a BASDAI score of <4 had a lower finger floor distance, a higher cervical rotation and modified Schober’s measurement values compared with patients with a BASDAI score of ≥4. There was a significant correlation between the BASDAI score and SF-36 subscores of physical function, physical role, bodily pain and emotional role (p<0.05). Conclusion: Clinical findings, functional disability, metrological measurements and quality of life are adversely affected by disease activity in AS. The subgroups of SF-36 subscores related to physical health show a more significant relationship with the disease activity in AS.